Tingkat Produksi dan Pendapatan Petani Kakao Pada Program Revitalisasi Kakao Kabupaten Kolaka Utara - Masitah, Masitah; Renaldi, Muh; Amin, Muhtar; Bustang, Bustang (Universitas Galuh, 2025)
The objective of this study is to determine the factors influencing cocoa production and income farmers receive from the cocoa revitalization program in Pakue Tengah district, Kolaka North regency. This study was conducted in Pakue Tengah District, Kolaka North Regency, from January to April 2025. The number of participants in this study was determined using the Slovin formula. Data analysis used Cobb-Douglas function analysis to determine the influence of production factors (land area, number of stands, labor, fertilizers and pesticides) on cocoa production and to conduct income analysis. The results of the study show that the coefficient of determination (R2) indicates the magnitude of influence of the variables land area (X1), number of stands (X2), labor (X3), fertilizers (X4) and pesticides (X5) on the dependent variable production (Y) is 0.849. This number is converted into a percentage, which means that the percentage contribution of the influence of the independent variables (land area, number of stands, labor, fertilizers, pesticides) on the dependent variable (production) is 84.9%, while the remaining 15.1% means that there are other factors affecting cocoa production that are not included in the research parameters. The results of the analysis of production factors influencing cocoa production in Pakue Tengah district show that the independent variables (land area, number of stands, labor, fertilizers, and pesticides) have a partially significant influence on the dependent variable (production). Only two variables, namely the number of stands and labor, have a significant impact on cocoa production in Pakue Tengah district, Kolaka North regency. The average income of cocoa farmers in Pakue Tengah district, Kolaka North regency, is IDR 11,207,569.56.